Effect of compression garments on the development of delayed-onset muscle soreness: A multimodal approach using contrast-enhanced ultrasound and acoustic radiation force impulse elastography - Heiss, R.; Kellermann, M.; Swoboda, B.; Grim, C.; Lutter, C.; May, M. S.; Wuest, W.; Uder, M.; Nagel, A. M.; Hotfiel, T. (Journal of Orthopaedic & Sports Physical Therapy, 2018)
Background: Delayed-onset muscle soreness (DOMS) is one of the most common reasons for impaired muscle performance in sports. However, little consensus exists regarding which treatments may be most effective, and the underlying mechanisms are poorly understood. Objectives: To investigate the influence of compression garments on the development of DOMS, focusing on changes in muscle perfusion and muscle stiffness. Methods: In this controlled laboratory study with repeated measures, muscle perfusion and stiffness, calf circumference, muscle soreness, passive ankle dorsiflexion, and creatine kinase levels were assessed in participants before (baseline) a DOMS-inducing eccentric calf exercise intervention and 60 hours later (follow-up). After DOMS induction, a sports compression garment (18-21 mmHg) was worn on 1 randomly selected calf until follow-up, while the contralateral calf served as an internal control. Muscle perfusion was assessed using contrast-enhanced ultrasound (peak enhancement and wash-in area under the curve), while muscle stiffness was assessed using acoustic radiation force impulse (shear-wave velocities). A magnetic resonance imaging scan of both lower legs was also performed during the follow-up testing session to characterize the extent of exercise-induced muscle damage. Comparisons were made between limbs and over time. Results: Shear-wave velocity values of the medial gastrocnemius showed a significant interaction between time and treatment (P = .006), with the noncompressed muscle demonstrating lower muscle stiffness values at follow-up compared to baseline or to the compressed muscle. No significant differences in soleus muscle stiffness were noted between limbs or over time, as was the case for muscle perfusion metrics (peak enhancement and wash-in area under the curve) for the medial gastrocnemius and soleus muscles. Further, compression had no significant effect on passive ankle dorsiflexion, muscle soreness, calf circumference, or injury severity, per magnetic resonance imaging. Conclusion: Continuous wearing of compression garments during the inflammation phase of DOMS may play an important role in regulating muscle stiffness; however, compression garments have no significant effects on intramuscular perfusion or other common clinical assessments.